GAMBARAN PENGETAHUAN MASYARAKAT TENTANG PROTOKOL KESEHATAN DAN KEPATUHAN MENJALANKAN PROTOKOL KESEHATAN PADA MASA PANDEMI COVID-19 DI KELURAHAN LANGGINI - Rinda Fithriyana; Alini Alini (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2021)
COVID-19 is a disease that currently affects the entire population of the world. Preventive efforts in the health protocols implemented by the community in breaking the chain of transmission of COVID 19 during the new normal period are by getting used to wearing masks, washing hands with soap (handsanitanizer), maintaining distance (social distancing), staying away from crowds and avoiding traveling outside the area. especially areas that have been declared as red zones. But in reality, they are not very obedient in implementing government appeals and instructions regarding health protocols in handling COVID 19. This study aims to describe the public's knowledge about health protocols and compliance with health protocols during the Covid-19 pandemic in Langgini Village. The design used in this research is descriptive analysis. The population in this study was the entire community in Langgini Village, Bangkinang Health Center Working Area, Kampar Regency with a total adult population of 3,885 people. The sampling technique used is simple random sampling with a total sample of 97 people. The data collection tool uses a questionnaire. Based on the results of the study, it is known that most of the respondents have good knowledge about health protocols, as many as 68 respondents (70.1%), most of the respondents comply with health protocols, as many as 59 respondents (58.8%). It is hoped that the health program manager will increase the provision of information regarding the importance of complying with health protocols to reduce the spread of COVID 19.